Towards Paperless Operation at the Outpatient Department of the Kuala Lumpur Hospital - Abd. Aziz, Osman (1997)
Patient care service is one of the most rapidly growing segments of the healthcare industry. It deals with the proper care of patients in a medical institution. The admission of a patient, restoring the patient to an acceptable health status and discharging the patient can be a very complex process. The trail of paperwork left is almost always overwhelming. This trail of paperwork tends to reduce the quality of care especially provided to the expecting patient. The erosion of the quality of care and efficiency becomes worse during read missions or referrals to other departments.The Outpatient Department is one of the busiest in the Kuala Lumpur Hospital It is also KLH's earliest tenant. That being so, it can be expected that the patient management would have been computerised or at the very least mechanised. The methodology employed seeks to clearly understand the current business processes, the complexity of the system and the underlying forces dictating the situation. Literature reviews on related subject matter formed the initial framework, concept and general direction. Surveying the Kuala Lumpur Hospital (KLH) landscape results in the Business Activity Map and used as a basis to identify suitable candidate for innovation. Within the confines of the Outpatient Department (OPD), understanding current process would expose the communication linkages between treatment, patient and other servicing centres. This is then followed by problem formulation, quantifying the delays, data sampling and deVelopment of the proto typed model. A comparison is also made between the methodology undertaken and established methodologies available. The data gathered indicated a high degree of inconsistencies although the recording protocol and reminders are available. This is to be expected in a predominantly manual data gathering environment where individual interpretation governs what is important and what is not.Results on data analysis reveals slight improvement in patient waiting time compared to the Quality Assurance 1994 report. This is attributed to differences in methodology employed and supporting structures available then. However on the whole, the average waiting time is still lengthy and therefore the need arises to identify the contributing factors thus bringing all processes in the OPD delivery service under detailed scrutiny. The application prototype was developed with the retention of core tasks in mind. All non-core activities are either removed or when still required are delegated as IT by-products.